Catch composition, reproductive biology and diet of the bramble shark Echinorhinus brucus (Squaliformes: Echinorhinidae) from the south‐eastern Arabian Sea. Issue 5 (30th August 2013) - Akhilesh, K. V.; Bineesh, K. K.; White, W. T.; Shanis, C. P. R.; Hashim, M.; Ganga, U.; Pillai, N. G. K.
<x xml:space="preserve">Abstract</x> Fishery and biological data are presented for the poorly known bramble shark Echinorhinus brucus (Squaliformes: Echinorhinidae), from the deep waters of the south‐eastern Arabian Sea. A total of 5318 individuals from by‐catch landings of deep‐water bottom set longlines, gillnets and shrimp trawl fisheries operating at depths of 200–1200 m were recorded between January 2008 and December 2011 at the Kochi Fisheries Harbour (Kerala). A total of 431 individuals, from 46 to 318 cm total length (LT) and 0·8 to 132 kg total mass (MT), were examined to determine biological data for this species. The LT at which 50% were mature (LT50) for females and males was estimated at 189 and 187 cm LT. Litter size ranged from 10 to 36 and size at birth was between 42 and 46 cm LT. Dietary analysis of stomach contents revealed E. brucus feeds on a variety of prey including crustaceans (69% index of relative importance, IRI), teleosts (25·8% IRI), cephalopods (1·7% IRI) and elasmobranchs (0·7% IRI). This study provides the first detailed biological data for this species and also highlights the extent of the by‐catch fishery for this species in Indian waters.